Does Prophylaxis Against Respiratory Syncytial Virus Infection Affect the Weight Percentiles of Infants with Hemodynamically Significant Congenital Heart Disease? - Ali Orgun; İbrahim İlker Çetin; Hazım Alper Gürsu (Galenos Publishing House, 2021)
Objective: The risk of severe respiratory syncytial virus (RSV) infection with significant morbidity and mortality is greatest in patients with hemodynamically significant congenital heart disease (hs-CHD). The humanized monoclonal antibody, palivizumab, was used as prophylaxis for RSV infection in children <24 months of age suffering from hs-CHD. We performed this study to evaluate the effects of RSV prophylaxis with palivizumab on the weight percentiles of infants with hs-CHD. Methods: During the RSV seasons between 2013 and 2017, children <24 months of age with hs-CHD who received ≥3 doses of palivizumab prophylaxis were included in this study. All patients were evaluated according to their weight percentiles examined at birth, at the first, and the last dose of palivizumab prophylaxis. The third percentile was accepted as the cut-off value of the lower weight percentile, and values below the 25th percentile were accepted as poorly controlled hs-CHD. Results: Sixty-one infants aged between 10 days and 15 months were included in the study. The infants received the first dose of palivizumab at the age of 5 months, and all infants received 4.56+-0.78 injections on an average. The number of patients weighing lower than the 25th percentile at the first, and the last dose of palivizumab were 36 (59 %) and 29 (47.5 %), respectively. A statistically significant difference was found between weight percentiles of infants at the first and the last dose of palivizumab (p<0.05). Discussion and conclusion: RSV prophylaxis with palivizumab affects weight percentiles positively, and it may help to reduce the hospitalization rate due to RSV infections in infants with hs-CHD.